Literatur Riview: Flavonoid Activity As an Anti-Cancer Compound - Hidayah, Himyatul; Widyaningsih, Andini; Pangestu, Anjani Dwi; Dewi, Siska Ratna (Universitas Malahayati, 2023)
ABSTRACT The activity of flavonoids as anti-cancer compounds has attracted the attention of researchers. Flavonoids are natural compounds found in various plants and have been identified as potential candidates for anti-cancer drugs. Flavonoids have multiple mechanisms of action, including inhibiting cancer cell growth, inducing apoptosis, and inhibiting the formation of new blood vessels. Flavonoids also possess antioxidant properties that protect normal cells from oxidative damage. In vitro and in vivo studies have demonstrated significant anti-cancer potential of flavonoids such as quercetin, kaempferol, genistein, and apigenin against various types of cancer, including breast, colorectal, lung, and prostate cancer. Moreover, flavonoids can enhance the effectiveness of conventional therapies and reduce their side effects, making them promising as adjuvant therapies in cancer treatment. However, further research is needed to gain a deeper understanding of the mechanisms of action of flavonoids, improve their bioavailability, and conduct clinical trials in humans. Exploring new sources of flavonoids and structural modifications can also enhance their anti-cancer activity. The application of advanced technologies and methods such as molecular biology, cell biology, and gene therapy can help uncover the full potential of flavonoids as anti-cancer compounds. Keywords: Flavonoid, Anti-Cancer Activity, Mechanisms of Action, Cancer Therapy, Quercetin, Kaempferol, Genistein, Apigenin. ABSTRAK Aktivitas flavonoid sebagai senyawa anti-kanker. Flavonoid merupakan senyawa alami yang ditemukan dalam berbagai tumbuhan dan telah menarik perhatian peneliti sebagai kandidat potensial untuk obat anti-kanker. Flavonoid memiliki berbagai mekanisme aksi, termasuk menghambat pertumbuhan sel kanker, menyebabkan apoptosis, dan menghambat pembentukan pembuluh darah baru. Flavonoid juga memiliki sifat antioksidan yang melindungi sel-sel normal dari kerusakan oksidatif. Penelitian in vitro dan in vivo telah menunjukkan bahwa flavonoid seperti quercetin, kaempferol, genistein, dan apigenin memiliki potensi anti-kanker yang signifikan pada berbagai jenis kanker, seperti kanker payudara, kanker kolorektal, kanker paru-paru, dan kanker prostat. Selain itu, flavonoid juga dapat meningkatkan efektivitas terapi konvensional dan mengurangi efek sampingnya, sehingga menjanjikan sebagai terapi tambahan dalam pengobatan kanker. Namun, penelitian lanjutan diperlukan untuk memahami lebih lanjut tentang mekanisme aksi flavonoid, meningkatkan bioavailabilitas, dan melakukan uji klinis pada manusia. Penggalian sumber-sumber baru flavonoid dan modifikasi struktural juga dapat meningkatkan aktivitas anti-kanker mereka. Penerapan teknologi dan metode terkini seperti biologi molekuler, biologi sel, dan terapi gen dapat membantu dalam mengungkap potensi penuh flavonoid sebagai senyawa anti-kanker. Kata Kunci: Flavonoid, Aktivitas Anti-Kanker, Mekanisme Aksi, Terapi Kanker, Quercetin, Kaempferol, Genistein, Apigenin